The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1186/s40345-017-0109-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between CRP genetic diversity and bipolar disorder comorbid complications

Abstract: BackgroundChronic low-grade inflammation is believed to contribute, at least in a subset of patients, to the development of bipolar disorder (BD). In this context, the most investigated biological marker is the acute phase response molecule, C-reactive protein (CRP). While the genetic diversity of CRP was amply studied in various pathological settings, little is known in BD.Methods568 BD patients along with 163 healthy controls (HC) were genotyped for the following single-nucleotide polymorphisms (SNPs) on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“… 81 , 84 Although a previous study also reported that the frequencies of the CRP polymorphisms were similar between the BD and control groups, the polymorphisms of CRP genetic diversity might contribute to the development of autoimmune comorbid disorders and rapid cycling, which are both representative of BD severity. 85 Taken together, the results from the study suggest that although polymorphisms of CRP might not be associated with plasma CRP levels in BD, polymorphisms could be linked to treatment outcome in cases of BD.…”
Section: Discussionmentioning
confidence: 73%
“… 81 , 84 Although a previous study also reported that the frequencies of the CRP polymorphisms were similar between the BD and control groups, the polymorphisms of CRP genetic diversity might contribute to the development of autoimmune comorbid disorders and rapid cycling, which are both representative of BD severity. 85 Taken together, the results from the study suggest that although polymorphisms of CRP might not be associated with plasma CRP levels in BD, polymorphisms could be linked to treatment outcome in cases of BD.…”
Section: Discussionmentioning
confidence: 73%
“…They concluded that low grade inflammation might play a role in mania and might be rather a state than a trait marker of bipolar disorder. Lastly, Boukouaci et al (2018) suggested that CRP genetic diversity may contribute to the development of auto-immune comorbid disorders and rapid cycling, both proxy of BD severity. They concluded that such findings might predict complex clinical presentations of the disease leading to precision medicine in psychiatry.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that these findings support a role of the altered peripheral immune response in RCBD. In a large cohort, some authors found that in a subgroup of patients, a CRP gene variant is associated with thyroid disorders and mostly with rapid cycling, especially in women (Boukouaci et al., 2018 ). Another study found higher levels of IL‐8, MCP‐1, IFN‐γ, IL‐6, TNF‐α in nonresponder depressed bipolar patients compared to responders (Benedetti et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%